2012
DOI: 10.1029/2012gl051645
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the missing source of glyoxal (CHOCHO) over China

Abstract: [1] Recent comparisons between satellite observed and global model simulated glyoxal (CHOCHO) have consistently revealed a large unknown source of CHOCHO over China. We examine this missing CHOCHO source by analyzing SCIAMACHY observed CHOCHO vertical column densities (VCDs) using a Regional chEmical trAnsport Model (REAM). This missing source is first quantified by the difference between SCIAMACHY observed and REAM simulated CHOCHO VCDs (DC CHOCHO ), which have little overlap with high biogenic isoprene emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
11

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 105 publications
(148 citation statements)
references
References 53 publications
8
129
11
Order By: Relevance
“…By comparing CHOCHO column densities derived from a global model simulation to satellite observations, Myriokefalitakis et al (2008) and Stavrakou et al (2009) speculate of a missing global source of CHOCHO. Similar study performed recently by Liu et al (2012) suggests that the missing CHOCHO sources in China is most likely due to the underestimation of aromatics in the VOC emission inventory. As first indicated by Volkamer et al (2007), if loss of CHOCHO on aerosol surfaces is not taken into account, models can substantially overestimate measured CHOCHO concentrations.…”
Section: Introductionsupporting
confidence: 82%
“…By comparing CHOCHO column densities derived from a global model simulation to satellite observations, Myriokefalitakis et al (2008) and Stavrakou et al (2009) speculate of a missing global source of CHOCHO. Similar study performed recently by Liu et al (2012) suggests that the missing CHOCHO sources in China is most likely due to the underestimation of aromatics in the VOC emission inventory. As first indicated by Volkamer et al (2007), if loss of CHOCHO on aerosol surfaces is not taken into account, models can substantially overestimate measured CHOCHO concentrations.…”
Section: Introductionsupporting
confidence: 82%
“…We used the 3D REAM to explore the missing mechanisms in the biosphere-chemistry-climate interactions. The REAM has been applied over North America, East Asia, and the Polar Regions (24,25,(44)(45)(46)(47)(48)(49). The model has a horizontal resolution of 36 km and 30 vertical layers in the troposphere.…”
Section: Methodsmentioning
confidence: 99%
“…Transport schemes (advection, convection, and turbulent mixing) are implemented by following previous work (50)(51)(52). SI Appendix, The chemical mechanism is adopted from GEOS-Chem v9.1 with updates on chemistry of aromatics (47), isoprene (54,55), and isoprene nitrates (56)(57)(58). It is noteworthy that recent studies (58) found that field measurements are consistent with relatively low NO x recycling efficiency (∼25%), resulting mainly from aerosol uptake, indicating that the impact of isoprene nitrate chemistry on surface ozone is much smaller than previously thought (56).…”
Section: Methodsmentioning
confidence: 99%
“…The major contributors among modeled species were also unmeasured aldehydes, glyoxal, methyl glyoxal and other secondary products, as shown in Table S6. Due to strong emissions of aromatics from solvent use and the petroleum industry in the PRD region (Zheng et al, 2009), high levels of glyoxal and methyl glyoxal in this region were observed from satellite measurements (Liu et al, 2012) and ground measurements . Compared to the 2006 measurements in Backgarden, a semirural site in the PRD region, the modeled glyoxal was twice as high as around 0.8 ppbV .…”
Section: Contributions To the Missing Reactivity: Secondary Vocsmentioning
confidence: 99%